Medieval and early modern religious cultures essays honouring Vincent Gillespie on his Sixty-fifth birthday - Ashe, Laura ca. 20./21. Jh; Hanna, Ralph (D. S. Brewer, 2019)
From the great age of pastoral expansion in the thirteenth century, to the revolutionary paroxysms of the English Reformation, England's religious writings, cultures, and practices defy easy analysis. The diverse currents of practice and belief which interact and conflict across the period - orthodox and heterodox, popular and learned, mystical and pragmatic, conservative and reforming - are defined on the one hand by differences as nuanced as the apophatic and cataphatic approaches to understanding the divine, and on the other by developments as profound and concrete as the persecution of declared heretics, the banning and destruction of books, and the emergence of printing. The essays presented in this volume respond to and build upon the hugely influential work of Vincent Gillespie in these fields, offering a variety of approaches, spiritual and literary, bibliographical and critical, across the Middle Ages to the Protestant Reformation and beyond. Topics addressed include the Wycliffite Bible; the Assumption of the Virgin as represented in medieval English culture; Nicholas Love and Reginald Pecock; and the survival of late medieval piety in early modern England. Contributors: Tamara Atkin, James Carley, Alexandra da Costa, Anne Hudson, Ian Johnson, Daniel Orton, Susan Powell, Denis Renevey, Michael G. Sargent, Annie Sutherland, Nicholas Watson, Barry Windeatt